Formation of a model of inter-industry balance in the management of economic systems. ("Journal "U". Economy. Management. Finance.", 2025)
The interindustry balance is a powerful tool for understanding and managing complex economic systems, providing a basis for informed decision-making and effective planning. This article examines the main functions and types of interindustry balances. The stages of using specialized software for constructing an interindustry balance are listed. Using the example of solving a specific economic problem, a model of the interindustry balance is formed, and the coefficients of direct material costs are calculated.
Keywords: input-output balance; forecasting; decision making; final product; gross product; direct cost coefficients